Gas stove use and respiratory health among adults with asthma in NHANES III - Eisner, M (BMJ Group, 2003)
Background: Gas stoves release respiratory irritants, such as nitrogen dioxide and other combustion by-products. Adults with asthma may be susceptible to the effects of gas stove exposure because of their underlying airway hyperresponsiveness, but this association has been difficult to establish. Aims: To examine the association between gas stove use and respiratory health. Methods: The analysis used data from the US Third National Health and Nutrition Examination Survey among 445 adults with asthma (representing 4.8 million persons with the condition). Results: Nearly half of the adults with asthma had a gas stove in their home (47.1%). There was no association between gas stove use and FEV(1) (mean change 146 ml; 95% CI -50 to 342 ml), FVC (0 ml; 95% CI -151 to 152 ml), or FEF(25%–75%) (357 ml; 95% CI -7 to 722 ml). There was also no relation between gas stove use and the risk of self reported cough (OR 0.8; 95% CI 0.4 to 1.7), wheeze (OR 1.5; 95% CI 0.7 to 3.2), or other respiratory symptoms. Controlling for sociodemographic, smoking, housing, and geographic factors did not appreciably affect these results. Conclusions: Among adults with asthma, there was no apparent impact of gas stove use on pulmonary function or respiratory symptoms. These results should be reassuring to adults with asthma and their health care providers.